The Effect of Migration on Productivity in OECD Countries - Schwarzová, Eva; Chytilová, Helena; Cingl, Lubomír, 1984-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
This bachelor thesis analyses the impact of the share of migrants from developed and developing countries in the total population on productivity in the destination country. The main contribution of the thesis is the analysis of this very distribution, which is not reflected in previous empirical literature despite the social perception of migrants according to their country of origin. It defines migrants according to their nationality to capture not only the first generation of migrants, but the overall network created. A panel was constructed for 10 developed OECD countries for the period 1996-2018, with total factor productivity capturing the productivity level in each country. Results of the model suggest that the increasing share of migrants from developed countries in the total population does not have a significant effect on productivity, while the share of migrants from developing countries affects productivity growth negatively. As a result, I conclude that the level of development of the origin countries affects the resulting impact of migrant share in the destination country.
Vedoucí práce: Helena Chytilová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses